Reproduce to preserve. From the disappearance of the original to the multiplied memory (TEST XY. Critical review of studies on the representation of architecture and use of the image in science and art, 2019)
In a far–seeing article published in Domus in September 1994, Franco Purini identified the ‘disappearance of the original’ as one of the intellectual questions posed by “the development of computer science applied to the representation of architecture”. The technical capability to reproduce works of art (and items of cultural heritage in general), thus freezing their appearance at a given moment in time, would apparently bring about a sort of immediate degradation of their value, as if the value of the original were partly lost to its replica and absorbed by it. Furthermore, such replication can be repeated indefinitely, with the effect of progressively abstracting most of the intrinsic value of the original itself, hypothetically to the extent of confusing it (one among many) amidst its myriad likenesses. Indeed, the independent character of such replicas can be so powerful that we could envisage their effective survival even in the absence of the originals themselves: we envisage the copy effectively taking over its model, replacing it in every role and functional context. But it is precisely in this ‘stand–alone’ quality of the replica with respect to its original that resides its potential as a ‘multiplier of memory’: having established a filial relationship with its model, it preserves the original’s identity while simultaneously transforming it and giving it substance, in perfect adherence to the profound meaning of the term ‘representation’. By ‘re–presenting’ the original, the replica projects its qualities in a new way. While manifestly differing from the model, the replica does not depreciate it; rather it adds layers of meaning and a deeper acquaintance, acquiring for itself the accolade of originality. This study lays down a critical framework for the theme of the reproduction of images (and architectural objects) in the digital age, expounding its scope by referencing a number of selected examples.